2009
DOI: 10.3390/molecules14062016
|View full text |Cite
|
Sign up to set email alerts
|

Pentacyclic Triterpene Distribution in Various Plants – Rich Sources for a New Group of Multi-Potent Plant Extracts

Abstract: Pentacyclic triterpenes are secondary plant metabolites widespread in fruit peel, leaves and stem bark. In particular the lupane-, oleanane-, and ursane triterpenes display various pharmacological effects while being devoid of prominent toxicity. Therefore, these triterpenes are promising leading compounds for the development of new multi-targeting bioactive agents. Screening of 39 plant materials identified triterpene rich (> 0.1% dry matter) plant parts. Plant materials with high triterpene concentrations we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
385
2
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 536 publications
(424 citation statements)
references
References 42 publications
18
385
2
4
Order By: Relevance
“…In addition, these consumption amounts have no clastogenic effect as assessed using clastogen induced micronucleated peripheral blood of mice. Our results are consistent with the previous study data indicating that mice which consumed extract from EF rich in triterpenoids didn't show any toxic effect (Jäger et al, 2009). This result suggested that high consumption of EF does not generate adverse effect on human health.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, these consumption amounts have no clastogenic effect as assessed using clastogen induced micronucleated peripheral blood of mice. Our results are consistent with the previous study data indicating that mice which consumed extract from EF rich in triterpenoids didn't show any toxic effect (Jäger et al, 2009). This result suggested that high consumption of EF does not generate adverse effect on human health.…”
Section: Discussionsupporting
confidence: 93%
“…PTs are synthesized mainly by the cyclization of oxidosqualene and squalene and exist in their free form or as components of saponins (glycosides) in many tropical and subtropical plants (Xu et al 2004;Jäger et al 2009). The compounds have attracted attention due to their remarkable biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of betulinic acid at concentrations up to 3 % (30 mg/g) in the external dried bark of plane tree (Platanus acerifolia L.) was previously reported [1,16,17]. These works focused in the extraction of betulinic acid from the bark of plane tree through conventional solid-liquid extraction with methanol, chloroform and heptane.…”
Section: Introductionmentioning
confidence: 99%
“…Triterpenic acids are secondary plant metabolites that are widespread in plants, mainly located in the peel, leave and stem bark [1]. They are part of the chemical family of isoprenoids, owning polycyclic structures of thirty carbon atoms, and presenting very low solubility in water and hydrophilic solvents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation